2000
DOI: 10.1051/analusis:2000280285
|View full text |Cite
|
Sign up to set email alerts
|

Gas and liquid chromatography-mass spectrometry of aldehydic products from lipid peroxidation

Abstract: Reactive species, especially those deriving from oxygen, produced during either physiological enzymatic reactions or particular conditions involving xenobiotics metabolism and pathological disorders, generate oxidative stress when physiological antioxidant defense mechanisms are overloaded. Oxidative stress leads to damages of biomolecules, such as lipids, proteins and nucleic acids. Lipid peroxidation is a degradation chain reaction of polyunsaturated fatty acids, which are easy targets of free radical attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For example, the formation of hexanal is proposed via linoleic acid cascade and arachidonic acid cascade through their hydroperoxides as intermediates by the lipoxygenase/fatty acid hydroperoxide lyase pathway. It could also be provided by oxidation from other polyunsaturated fatty acids, as well as heptanal [ 54 ]. Lower aliphatic alcohols may be formed by decomposition of secondary hydroperoxides of fatty acids by the reduction of the corresponding aldehydes [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the formation of hexanal is proposed via linoleic acid cascade and arachidonic acid cascade through their hydroperoxides as intermediates by the lipoxygenase/fatty acid hydroperoxide lyase pathway. It could also be provided by oxidation from other polyunsaturated fatty acids, as well as heptanal [ 54 ]. Lower aliphatic alcohols may be formed by decomposition of secondary hydroperoxides of fatty acids by the reduction of the corresponding aldehydes [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…These aldehydes are widespread, as they have already been found in many other sea products, such as green and brown macroalgae (refs 5 and 13, respectively), lobsters (28) and oysters (12,29). When studying by GC-MS and LC-MS, the aldehydes produced by lipid peroxidation, Enoiu et al (30) demonstrated that hexanal and 2-(E)-hexenal could come from linolenic acid, a ω3 PUFA. They also could arise from other ω3 PUFAs such as C20:5ω3 (31), which have been reported as the most likely substrates for enzymatic oxidation, producing mainly aldehydes and alcohols.…”
Section: Optimization Of Dynamic Headspace Extractionmentioning
confidence: 95%
“…Thus, we could conclude that eicosapentaenoic acid was probably the precursor of these two volatile compounds. Hexanal could also be provided by oxidation from linoleic acid (30) or other ω6 PUFAs, as well as heptanal. As Palmaria palmata contains both linoleic and arachidonic acids (32,33), the detection of these compounds was not surprising.…”
Section: Optimization Of Dynamic Headspace Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid increase in the concentrations of reactive oxygen species (ROS) such as superoxide, hydrogen peroxide, singlet oxygen and the hydroxyl radical may have direct and indirect roles in the stress response, such as acting as an antibiotic agent and controlling gene expression (Kotchoni & Gachomo 2006). Many oxygenated VOCs important in atmospheric chemistry such as formaldehyde, acetone and acetaldehyde are major products of lipid peroxidation by ROS (Dennis & Shibamoto 1990;DeZwart et al 1997;Enoiu et al 2000;Orhan et al 2006;Shibamoto 2006). Although extensively used as biomarkers for lipid oxidation in animals, including humans, their production in stressed plants via this mechanism has not previously been demonstrated.…”
Section: A Summary Of the Dmentioning
confidence: 99%